Antibacterial effect of electrospun polycaprolactone/polyethylene oxide/vancomycin nanofiber mat for prevention of periprosthetic infection and biofilm formation. Issue 8 (August 2015) - Jang, Chul Ho; Cho, Yong Beom; Jang, Yoon Seok; Kim, Min Seong; Kim, Geun Hyung
Abstract Objective In this study, we developed a biocompatible and biodegradable vancomycin (VM)-eluting electrospun poly(ɛ-caprolactone) (PCL)/polyethylene oxide (PEO)/VM/PCL nanofiber mat. The purpose of this study was to evaluate the efficacy of this nanofiber mat for preventing methicillin-resistant Staphylococcus aureus (MRSA) biofilm on the ossicular prostheses and otitis media. Materials and methods Fabrication of VM eluting nanofiber mat was carried out using PCL and PEO. The release of VM was assessed by spectrophotometry in vitro. The antibacterial effect was evaluated by inhibition zone test and biofilm formation test in vitro. And prevention of MRSA infection by guinea pig was assessed by otoendoscopy, temporal bone CT and histopathologic examination in vivo. Results VM released followed a triphasic pattern. VM eluting nanofiber mat prevented MRSA biofilm formation on the surface of ossicular prostheses regardless of materials in vitro, and MRSA otitis media in vivo. Otoendoscopy, temporal bone CT, and histopathologic findings revealed well ventilated middle ear. Conclusion From these results, VM eluting nanofiber mat may be a promising method for prevention of MRSA periprosthetic infection and biofilm formation.